PELANGGARAN PERATURAN LALU LINTAS OLEH PENGENDARA SEPEDA MOTOR RODA DUA DI WILAYAH POLISI SEKTOR UJUNG BATU KABUPATEN ROKAN HULU - Saurmaida Sibarani; Risdayati " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
Violation of traffic rules by motorcycle rider two in the area Police Sector Ujung Batu often once happened. As for the the violation of which often made is the completeness of the vehicle, the completeness of papers, helmet, against the flow, to violate the regulations, the speed limit on the maximum, don’t turn on the main lights in the daytime.This research done to find out hoe the characteristics of a society that violate the rules of traffic in the area Police Sector Ujung Batu, Rokan Hulu Regency and what factors causes of motorcycle riders of violation of the rules of traffic in the area Police Sector Ujung Batu, Rokan Hulu Regency.The Theory is in use in this research is the theory of irregularities. Any traffic violations commited by the motorcycle rider two wheels including the abberant behavior, aberrant behavior on here any behavior that violates the norms of society or group. Data collection techniques in use here the first observation of the writer make research directly to the field to get the data in need in research, second interview with democracy, researchers have been equip with a detailed list of questions.Character research results of violation of the respondents based on gender, most of the men from theage of 16-50, tribe of themost violated is malay, educational level respondents ranging from elementary scholl until collage. Respondents does violate the traffic the most dominant is the lack of respondents who follow socialaziation about traffic rules that don’t understand the importance of the trafficregulations for the safety of the riders, signpost traffic sign already exists but it doesn’t work effectively, carried out the street sign is often dead, and is not working. And the way we accept swordfish in accordancewith the offenses of motorcycle riders do not cease to give effect ti some of the riders of violation of traffic.Keywords : Violations of traffic rules, motorcycle rider two wheels.